Suspicion of Postanesthetic Femoral Paralysis of the Non-Dependent Limb in a Horse - Mirra, Alessandro; Klopfenstein Bregger, Micaël David; Levionnois, Olivier Louis (Frontiers in Veterinary Science, 2018)
A 15-year old Selle Francais gelding was presented to the equine referral hospital for treatment of a left guttural pouch mycosis previously diagnosed. After induction the horse was shortly hoisted by all four feet, moved on a padded surgical table and positioned in right lateral recumbency. In order to reduce the risk of bleeding during surgical manipulation of the carotid and maxillary arteries, a mean arterial pressure between 60 and 70 mmHg was targeted. After surgery, the horse was moved in a padded recovery box keeping the same lateral recumbency. Four unsuccessful attempts were performed, with the horse always returning to sternal recumbency keeping the left hind limb up. At the fifth attempt, performed 120 minutes after the end of the general anesthesia, the horse stood up correctly but moderate ataxia and absence of weight bearing on the left hind limb were shown. Both the stifle and the fetlock joint were held in a flexed position and could not be extended properly in order to set the foot on the ground, resulting in a very short step. The horse was calm, not sweating and willing to move; the muscles of the affected limb were relaxed, and the limb was neither warm nor painful at palpation. Occasionally, the horse flexed the affected hind limb in an exaggerated motion with marked abduction. No additional laboratory analyses were performed. Due to a strong suspicion of neuropathy, a sling support was initiated and a supportive bandage associated with flunixine administration was performed until resolution of the symptoms. The horse fully recovered after 3 days. This case report does not clarify the pathogenesis of the possible post-anesthetic neuropathy accounted on the nondependent limb, highlighting the need for future research in this field. Nondependent limb neuropathy should be an expected problem even after having ruled out the most commonly known causes predisposing to post-anesthetic lameness.